Normal Values for Parotid Gland and Submandibular-Sublingual Salivary Gland Complex Uptake of 99mTechnetium Pertechnetate using SPECT in Mice with Respect to Age, Sex, and Circadian Rhythm - Huang, Eleonore L.; Steffen, Ingo G.; Lukas, Mathias; Huang, Kai; Aschenbach, Joerg R.; Eary, Janet F.; Brenner, Winfried; Beindorff, Nicola (Nuklearmedizin - NuclearMedicine, 2019)
Aim The aim of this study was to establish normal values for parotid gland (PG) and submandibular-sublingual salivary gland complex (SSC) uptake of 99mtechnetium pertechnetate (99mTcO4) as a function of age, sex and circadian rhythm in mice.Methods In 12 female (F) and 12 male (M) C57BL/6N mice, nine consecutive SPECT images of 10 min each were acquired as dynamic acquisitions beginning 5 min after intravenous injection of 80 MBq 99mTcO4. Each mouse was imaged in follow-up studies at 1, 3, 6, 12 and 24 months of age. In order to assess for physiologic changes related to circadian rhythm, animals were imaged during light (sleeping phase) as well as during night conditions (awake phase). The percentage tracer uptake of the injected activity is expressed as median %ID.Results Maximum 99mTcO4 uptake occurred earlier in PG at 11 min compared to SSC at 79 min (p < 0.001). No significant effect of circadian rhythm was observed in PG (p = 0.64) and SSC uptake (p = 0.27). With aging, 99mTcO4 uptake significantly decreased for PG (p < 0.001) while it increased for SSC (p < 0.001). F (0.5) had a significantly higher PG uptake than M (0.3; p < 0.001) up to an age of 24 months. However, SSC uptake of F (4.6) was higher than that of M (3.8; p = 0.014) only at the age of 1 month. Thereafter, F (5.6) had lower SSC uptake than M (9.2; p < 0.001) from 3 months onwards. Normalizing %ID to gland volume showed that F had a significantly higher uptake (%ID/mm3) in both PG (F 0.013; M 0.007; p < 0.001) and in SSC (F 0.110; M 0.075; p < 0.001).Conclusion Uptake patterns differed among PG and SSC with a significant impact of age and sex while circadian rhythm had no significant influence. Therefore, design of salivary gland studies in mice using 99mTcO4 should consider age and sex as relevant factors.
Keywords: parotid gland; submandibular-sublingual salivary gland complex; technetium uptake; SPECT; age; sex; circadian rhythm; mice